Effect of low ionic strength on anti-Pr reactions - Leo, Albrecht; Kreft, Heidi; Hack, Hildegard; Roelcke, Dieter (Beiträge zur Infusionstherapie und Transfusionsmedizin, 1996)
The effect of low ionic strength (LIS) on 28 anti-Pr, 20 anti-I and 20 anti-i cold agglutinins was investigated. The reaction of the anti-Pr CAs varies markedly. In most cases LIS has an enhancing effect. In some cases the thermal amplitude was widened so far that the reaction at 37 degrees C under LIS was stronger than at 0 degree C in PBS. With regard to the anti-Pr subspecificities anti Pr1, -Pr2 and -Pr3 or to the distinction of the immunodominant NeuNAc group (alpha a2,6- or alpha 2,3-bond) a correlation between these characteristics and the reaction in LIS could not be identified. The anti-I are not influenced by LISS, anti-i in a few cases. The reason for the variable reaction of the anti-Pr remains unclear. To further elucidate the LISS effect on anti-Pr, the contribution of the antibody structure should be regarded, but data for the use of H- and L-chain genes in anti-Pr are sparse. For compatibility testing in the routine laboratory, LISS-sensitive anti-Pr may play a role in disturbing the screening for RBC antibodies.